PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN DARING DENGAN MENGGUNAKAN POWTOON DAN SCREENCASTIFY - Munirul Ula; Sayed Fachrurrazi; Rizky Putra Phonna; Yessi Apprilia (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
In time of the Covid-19 pandemic, with the necessity to run online lectures, there are obstacles in designing an online learning media that is easy to use by teachers and easy to understand by students. This community service program provides training on how to make learning videos by utilizing the Powtoon and Screencastify applications for teachers which is carried out by mentoring to improve teacher abilities. The sustainability of the program is fully returned to the teachers who participated in the training to continue the implementation of this learning application after the program is finished. From the results of the questionnaire evaluating the results of the training, it can be seen that there are positive results in terms of increasing competitiveness and values ​​in the field of education for fostered partners. This is shown by when the material is delivered, participants are given the option to practice making learning videos in groups and individually using the Powtoon and Screencastify applications. The participants were very enthusiastic about participating in this training. This is because they have just used these two applications for making learning videos. All of them were satisfied with this activity and the participants hoped that there would be retraining activities in the future.